(untitled) (Scientific journal of the Fergana State University, 2026)
This article explores the origin of the term “lost generation,” which emerged in Western literature in the first half of the 20th century, and its use in portraying the protagonists of literary works. The depiction of characters belonging to this generation in Erich Maria Remarque’s novel Three Comrades is analyzed. In this work, the author gives deep artistic expression to the tragic consequences of war on humanity. Through the image of the “lost generation,” the writer reflects on the spiritual void, aimlessness, lost dreams, and the decline of life values in society. The emotional experiences of the protagonists can also be studied in parallel with modern anti-war works in Uzbek literature. Such literary analyses today serve as important tools for educating the younger generation in an anti-war spirit and promoting the ideas of peace and humanism.